Pemaknaan Generasi Z Terhadap Perselingkuhan Dalam Film Norma Antara Mertua dan Menantu - Putri, Aninditya Ariska; Basori, Muhamad Hasan (Universitas Muhammadiyah Magelang, 2026)
This study aims to analyze Generation Z’s reception of the representation of infidelity in the film Norma Antara Mertua dan Menantu using Stuart Hall’s encoding”“decoding theory. This research employs a qualitative approach with a reception analysis method. Data were collected through in-depth interviews with nine Generation Z informants who had watched the film. The findings show that 55.6% of informants occupy the dominant hegemonic position, fully accepting the film’s moral message and interpreting Norma as the most psychologically affected character. Meanwhile, 33.3% fall into the negotiated reading position, accepting the main message but interpreting the conflict resolution contextually. The remaining 11.1% are categorized in the oppositional reading position, showing resistance toward certain character representations and constructing alternative meanings.